2021
DOI: 10.1038/s43246-021-00185-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of defect formation during atomically precise desulfurization of monolayer MoS2

Abstract: Structural symmetry-breaking is a key strategy to modify the physical and chemical properties of two-dimensional transition metal dichalcogenides. However, little is known about defect formation during this process. Here, with atomic-scale microscopy, we investigate the evolution of defect formation in monolayer MoS2 exposed indirectly to hydrogen plasma. At the beginning of the treatment only top-layer sulfur atoms are removed, while vacancies and the molybdenum atomic layer are maintained. As processing cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 71 publications
1
38
0
Order By: Relevance
“…However, defects in MoS 2 , in particular, the vacancy defects, could strongly alter the position of both the modes. Studies show that a significant frequency decrease of the E 1 2g mode occurs, as the restoring force constant is dramatically reduced by the creation of sulfur vacancies. While we attribute the observed downshifting of E 1 2g mode in sample B due to unpassivated sulfur vacancies based on the findings from PL results (will be discussed later), the splitting of the A 1g mode, which is rarely observed in monolayer MoS 2 previously, needs to be understood and will be addressed later.…”
Section: Resultsmentioning
confidence: 83%
“…However, defects in MoS 2 , in particular, the vacancy defects, could strongly alter the position of both the modes. Studies show that a significant frequency decrease of the E 1 2g mode occurs, as the restoring force constant is dramatically reduced by the creation of sulfur vacancies. While we attribute the observed downshifting of E 1 2g mode in sample B due to unpassivated sulfur vacancies based on the findings from PL results (will be discussed later), the splitting of the A 1g mode, which is rarely observed in monolayer MoS 2 previously, needs to be understood and will be addressed later.…”
Section: Resultsmentioning
confidence: 83%
“…It was reported that exposure to low-energy remote H 2 plasma resulted in the removal of sulfur atoms in MoS 2 . 31 Accordingly, the composition of the grown MoS 2 was examined. Despite this concern, the S/Mo atomic ratio of the films was very close to the stoichiometric value, irrespective of the injection of H 2 plasma (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Remote hydrogen plasma treatment has recently demonstrated its utility to introduce sulfur vacancy defects in MoS2 under a controlled manner 43 . Figure 4b and 4g are exemplary input STEM images of as-synthesized MoS2 and plasma-treated MoS2, respectively.…”
mentioning
confidence: 99%
“…As shown in Figure 4k and 4m, the intensity histogram at localized atomic sites typically shows two strong peaks; a peak at the center position of 1.0 is from double occupancy of sulfur atoms and another peak at around 1.5 is from Mo atom sites. A small shoulder peak at a center of around 0.7 is attributed to VS1 sites 43 . The fact that the shoulder peak increases in the plasma-treated samples is consistent with this interpretation.…”
mentioning
confidence: 99%
See 1 more Smart Citation